Social media interfaces as a representation of cultural meanings - Shchekoturov A. V. (Слово.ру: балтийский акцент, 2018)
A problem of the growing popularity of cross-cultural social media studies is the lack of discrimination between the effects of user characteristics and those of the architecture of a virtual platform interface. This makes the detected cultural differences unreliable. A way to solve this problem is a comparative study of social media interfaces only, seeking to identify the culturally constituted meanings embedded in the design of virtual platforms. These meanings are employed in the users’ virtual self-presentation. I analysed Facebook and VKontakte – two large social media platforms originating from the countries with different cultural values and social expectations. My focus was on the principal categories of identification and virtual self-presentation. These are gender, sexuality, marital status, attitudes, and personal preferences. The comparative analysis of interfaces was carried out from the perspective of a change in the linguistic projection (which happens when the user switches from Russian to English and vice versa). I detected significant differences in all the categories analysed. I conclude that the Vkontakte platform reflects traditional patriarchal values and the Facebook platform those of pluralism and subject-centricity.